A Revised Kamal Integral Transformation Method for Solving First-Order Nonlinear Fractional Differential Equations - Uba, Nura; Adamu, M. M.; Abdulhameed, M.; U, Hafsat Y.; O, Okai J. (YASIN, 2025)
This study integrates the Kamal transform method with Adomian polynomials to provide approximate analytical solutions for non-linear fractional differential equations. Since the Kamal transform alone cannot handle non-linear terms, Adomian polynomials are used to decompose these terms. The resulting solutions are compared with those from other methods applied to the same problems. The results show that the solution obtained with the Kamal transform and Adomian polynomial closely aligns with those from other methods, demonstrating the effectiveness of this combined approach. This work emphasizes the strength of the Kamal transform method and Adomian polynomials as integral transform techniques for solving non-linear equations.